2013
DOI: 10.1371/journal.pone.0055370
|View full text |Cite
|
Sign up to set email alerts
|

Blood Agar Validation for Susceptibility Testing of Isoniazid, Rifampicin, Ethambutol, and Streptomycin to Mycobacterium tuberculosis Isolates

Abstract: In recent studies, it was shown that blood agar can be used at least as effectively as Löwenstein-Jensen medium for growing Mycobacterium tuberculosis. It was also shown that susceptibility testing can be performed on blood agar. Additional validation of blood agar was performed on regional M. tuberculosis isolates from Turkey to determine critical concentrations of isoniazid (INH), rifampicin (RIF), ethambutol (ETM), and streptomycin (STR). In the current study, 40 M. tuberculosis clinical isolates were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Although antitubercular DSTs are carried out mainly using the standard proportional method on L–J medium and Middlebrook 7H10 agar, they have many disadvantages. In addition to the inactivation of heat-labile drugs [8], [10], reduction of drug activity can occur because of (a) binding of the drug to the agar (agar-based mediums), or proteins and phosphate of egg (egg-based mediums) [10], [11], [19], [20]; (b) prolonged incubation time, which potentially reduces the potency of certain antimicrobials; and (c) less contact of organisms with appropriate concentrations of antimycobacterial substances on solid media [8], [9]. Although, the two lipophilic compounds (derivative of dihydropyridines) tested in this study have relative heat stability, the above-mentioned disadvantages of L–J medium (all or in part) might explain their inactivation in the standard method.…”
Section: Discussionmentioning
confidence: 99%
“…Although antitubercular DSTs are carried out mainly using the standard proportional method on L–J medium and Middlebrook 7H10 agar, they have many disadvantages. In addition to the inactivation of heat-labile drugs [8], [10], reduction of drug activity can occur because of (a) binding of the drug to the agar (agar-based mediums), or proteins and phosphate of egg (egg-based mediums) [10], [11], [19], [20]; (b) prolonged incubation time, which potentially reduces the potency of certain antimicrobials; and (c) less contact of organisms with appropriate concentrations of antimycobacterial substances on solid media [8], [9]. Although, the two lipophilic compounds (derivative of dihydropyridines) tested in this study have relative heat stability, the above-mentioned disadvantages of L–J medium (all or in part) might explain their inactivation in the standard method.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, Coban et al reported the susceptibility of the bacteria to Isoniazid, rifampicin, ethambutol, and streptomycin antibiotics using Blood Agar Validation for TB. 11 Hall et al presented an AST of resistant TB using microtiter assay. 12 These methods are quite safe, however; the main limitations are low sensitivity, complex sample preparations, lack of automation, and growth dependence.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, Coban et al. reported the susceptibility of the bacteria to Isoniazid, rifampicin, ethambutol, and streptomycin antibiotics using Blood Agar Validation for TB 11 . Hall et al.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial susceptibility tests (ASTs) are mainly examined by traditional methods like disk diffusion, dilution (agar and broth) and E-test. In the literature, Coban et al reported the susceptibility of the bacteria to Isoniazid, rifampicin, ethambutol, and streptomycin antibiotics using Blood Agar Validation for MTB [11]. Hall et al, presented an antimicrobial susceptibility test of resistant MTB using microtiter assay [12].…”
Section: Introductionmentioning
confidence: 99%